2018
DOI: 10.2298/sarh161121002a
|View full text |Cite
|
Sign up to set email alerts
|

Trends in incidence of non-melanoma and melanoma skin cancers in central Serbia

Abstract: Introduction/Objective The incidence of both melanoma and non-melanoma skin cancers (NMSC) has been increasing over the past decades worldwide. NMSC is the most common cancer in white population and melanoma is one of the deadliest cancers today. The objective of the paper was to determine trends in age-standardized incidence rates of NMSC and melanoma in central Serbia from 1999 to 2013. Method A descriptive epidemiological study was done. Data about incidence for NMSC and melanoma were obtained from the Serb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Melanoma is the most deadly skin cancer and due to its increasing incidence, particularly in the most developed countries, it represents a great challenge for primary prevention. Despite its being less common than non-melanoma skin cancer, it is one of the most invasive and treatment-resistant skin cancer [29]. The existing therapy of melanoma is very expensive and it could be used in some patients with predisposition for the good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Melanoma is the most deadly skin cancer and due to its increasing incidence, particularly in the most developed countries, it represents a great challenge for primary prevention. Despite its being less common than non-melanoma skin cancer, it is one of the most invasive and treatment-resistant skin cancer [29]. The existing therapy of melanoma is very expensive and it could be used in some patients with predisposition for the good outcome.…”
Section: Discussionmentioning
confidence: 99%
“…This national register-based study analyzes the trends of NMSC over a period of 17 years and it is one of the few studies (18,22) describing the incidence of NMSC in the Serbia. Our study showed that NMSC is the most common among the elderly; the age-specific incidence rates is the highest in the age group over 70 years (50%) and very low in the younger age (3%).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, Euromelanoma as a pan-European prevention programme against NMSC and melanoma started in 1999 and spread in 33 countries (Serbia included) (19,20,21). However, public health significance of NMSC seems to be unrecognized in Serbia, there is no national prevention strategy for control this cancer and only a few studies reported incidence rate of NMSC in Serbia (18,22).…”
Section: Introductionmentioning
confidence: 99%
“…The results of a Romanian study showed that patients suffering from basal cell carcinoma were occupationally exposed to UV radiation [35]. In the Republic of Serbia (RS), the occurrence and number of skin cancer cases has been increasing lately, along with other forms of cancers, but also the methods for their detection are becoming increasingly successful [36,37,38]. The Rulebook on Determination of Occupational Diseases (Official Gazette of the Republic of Serbia, no.…”
Section: Implementation Of the Montreal Protocol And The Positive Effmentioning
confidence: 99%